Management of a Traumatic Wound in a Malnourished Orphan Asian Baby Elephant (Elephas maximus) (International Journal of Natural Sciences, 2016)
The present case report was carried out to evaluate the outcome of traumatic wound in a malnourished orphan elephant calf. A 1.5 month old, female Asian Elephant calf approximate weighing 100 kg, was admitted to the Teaching Veterinary Hospital, Chittagong Veterinary and Animal Sciences University, Bangladesh, with a history of squeezed and trapped in natural tree during foraging, detached from the herd, rescued by nearest forest people and treated by local veterinarian. The baby elephant was dull, depressed, dehydrated and emaciated on clinical examination. A local swelling (65 cm) was noticed on left hind limb(stifle joint) and a circular wound on lateral aspect of the limb where mild discharge was noticed. Gait and posture was not normal. Wound swab, blood and fecal sample were collected and sent to the respective departments. Pyogenic organisms were found in wound swab culture. Blood parameters revealed lower value of TEC, Hg, PCV, glucose and total protein. No parasite or ova were found in fecal sample. The elephant calf was fed with powder milk as 10% of total body weight (10 liters/day at 1 hour interval). Ceftriaxone sodium @ 20 mg/kg bwt along with pain killer ketoprofen @ 3 mg/kg bwt, amino acid solution @20 ml hematinic preparation @10 ml , vitamin ADE preparation @10 ml along with 5% dextrose saline (2liters/day), local application of Dressgel ointment (herbal preparation) and wound dressing with povidone iodine at regular interval as required until healing. The calf revealed improved condition such as more active and alert, improved gait, reduced local swelling and no discharge from the wound. The CBC and serum biochemical parameter was also improved by day 4 while the calf was shifted to Dulahazra safari park, Chokoria, Chittagong.International Journal of Natural Sciences (2015), 5(1) 21-25